2011
DOI: 10.1007/s10620-011-1979-1
|View full text |Cite
|
Sign up to set email alerts
|

Emu Oil Increases Colonic Crypt Depth in a Rat Model of Ulcerative Colitis

Abstract: Emu oil improved tissue damage associated with colitis, suggesting its potential as a unique formulation to augment conventional treatment approaches for IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 33 publications
8
61
0
Order By: Relevance
“…This was evident in the scoring pattern of the ulcers, where the groups treated with emu oil alone or in combination with aloe vera has showed reduced ulceration and in some complete absence of ulcers, resulting in better scores than sulfasalazine. Similar findings were reported in earlier studies [8,16].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This was evident in the scoring pattern of the ulcers, where the groups treated with emu oil alone or in combination with aloe vera has showed reduced ulceration and in some complete absence of ulcers, resulting in better scores than sulfasalazine. Similar findings were reported in earlier studies [8,16].…”
Section: Resultssupporting
confidence: 93%
“…[8][9][10][11][12][13].Aloe vera, a plant product, has been found to be effective in clinical trial for the treatment of IBD [14]. So, the present study selected aloe vera for comparison along with sulfasalazine [Positive control].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water was used as the control based on previous studies (1,24) involving the use of 5-FU and EO for the same duration of time, in which no significant differences in the body weight gain of rats were found between the water-treated group and the EO-treated group. In addition, since to date there is no information available on the relationship between EO bioactivity, metabolism, and body weight, a set amount (unadjusted by body weight) of emu oil (1.0 ml/day, a Specimen collection.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies comparing different oils showed that EO was most potent in reducing adjuvant-induced dermal inflammation (53). More recently, dietary EO supplementation has been shown to be efficacious at reducing intestinal tissue damage and inflammation caused by 5-FU chemotherapy (1,24). However, whether EO can protect bone from inflammatory bone loss during chemotherapy remains unknown.…”
mentioning
confidence: 99%